Dark-Induced Barley Leaf Senescence – A Crop System for Studying Senescence and Autophagy Mechanisms - Paluch-Lubawa, Ewelina; Stolarska, Ewelina; Sobieszczuk-Nowicka, Ewa (Frontiers in Plant Science, 2021)
This review synthesizes knowledge on dark-induced barley, attached, leaf senescence (DILS) as a model and discusses the possibility of using this crop system for studying senescence and autophagy mechanisms. It addresses the recent progress made in our understanding of dark-induced leaf senescence. The following aspects are discussed: the importance of chloroplasts as early targets of DILS, the role of Rubisco as the largest repository of recoverable nitrogen in leaves senescing in darkness, morphological changes of these leaves other than those described for chloroplasts and metabolic modifications associated with them, DILS versus developmental leaf senescence transcriptomic differences, and finally the observation that in DILS autophagy participates in the circulation of cell components and acts as a quality control mechanism during senescence. Despite the progression of macroautophagy, the symptoms of degradation can be reversed. In the review, the question also arises of how plant cells regulate stress-induced senescence via autophagy and how the function of autophagy switches between cell survival and cell death.